A qualitative inquiry: management of recidivism in South Africa - Samuels, Jerome A. (Crime, law and social change, 2024)
At a high cost to the community and taxpayers, offenders frequently return to correctional facilities shortly after being released. In South Africa, the management of recidivism has not been researched extensively, and recidivism as a phenomenon has received scant attention. This study explores how the Department of Correctional Services in South Africa manages recidivism using the perspectives of staff and external stakeholders. A qualitative study was conducted with 19 Department of Correctional Services employees and ten external stakeholders. The findings postulate that South Africa’s Department of Correctional Services (1) lacks defined policy guidelines, processes, or structure for addressing recidivism; (2) suggests a gap in the system as departments work independently within the Justice, Crime Prevention and Security Cluster (JCPS), which includes, among others, the Departments of Police, Home Affairs, Justice and Correctional Services; (3) recommends that the computer systems of the JCPS be integrated to manage recidivism, and the use of a criminal record number for the detection of recidivists; (4) identifies a need for the development of policy, policy procedures, and guidelines for managing repeat offending; and (5) a need for coherent research on the management of recidivism of offenders within the Department of Correctional Services in South Africa.